Impelementasi Program Digitalisasi pada Dinas Kearsipan dan Perpustakaan Kota Mataram - Ali, Muhammad; Erlambang, Nanda; Salsabila, Elvira Hilwa; Jailani, Muhammad Aprian (Universitas 17 Agustus 1945 Surabaya, 2023)
The Mataram City Archives and Library Service (Diarpus) is one of the Regional Technical Institutional Organizations responsible for organizing archives to form a national integrated archive management system. This research aims to determine how far the use of the Srikandi Application in implementing e-government is to improve the quality of research services. This uses a descriptive qualitative approach to produce information. Determining informants uses a purposive sampling technique, namely a data source sampling technique including the head of utilization and archival services development in analyzing data using the Miles & Huberman Interactive Analysis Model which can be visualized as follows: Data Collection, Reduction, Data Presentation, The conclusion that is used as a reference for researchers in the theory put forward by Edwards III is that there are four variables in public policy, namely Communication, Resources, Implementing Attitudes and Bureaucratic Structure. It can be concluded that the inhibiting factors are employees' lack of understanding in implementing their duties and responsibilities and human Resources (HR). ) is still considered lacking or limited, and infrastructure is still somewhat lacking. Researchers' suggestions for implementing Electronic Government through an Integrated System (SRIKANDI) in the Mataram City archives and library service, namely increasing the provision of facilities, including infrastructure, and providing training or private practice to employees who are still in a situation where they are technologically illiterate and have difficulty using the SRIKANDI application